Correlation Between Plasma Levels of RIP3 and Acute Ischemic Stroke with Large-Artery Atherosclerosis - Chen, Beilei; Hang, Jing; Zhao, Yuanyuan; Geng, Yang; Li, Xiaobo; Gu, Zhie; Li, Jun; Jiang, Chao; Tao, Luhang; Yu, Hailong (Current Neurovascular Research, 2022)
Background: Receptor-interacting serine-threonine protein kinase 3 (RIP3) was previously discovered to be an important medium in the occurrence and development of major atherosclerotic cerebral infarction. However, the role of RIP3 in acute ischemic stroke remains unclear. Objective: This study aimed to explore the correlation between plasma levels of RIP3 and acute ischemic stroke with large-artery atherosclerosis (LAA). Methods: This prospective study enrolled 116 patients with LAA, 40 healthy controls, and 30 acute ischemic stroke patients with small-artery occlusion. The patients with LAA were divided according to the quartile of plasma levels of RIP3. A logistic regression model was used for comparison. The ROC curve was performed to evaluate the predictive value. Results: In patients with LAA, the RIP3 levels in patients with poor outcomes as well as neurological deterioration were significantly higher than those with good outcomes (P < 0.001) and without neurological deterioration (P = 0.014). Patients in the highest levels of plasma RIP3 quartile were more likely to have neurological deterioration (OR, 11.07; 95% CI, 1.990-61.582) and poor outcomes (OR, 35.970; 95% CI, 5.392-239.980) compared with the lowest. The optimal cut-off value for neurological deterioration was 1127.75 pg/mL (specificity, 66.7%; sensitivity, 69.2%) and that for poor prognosis was 1181.82 pg/mL (specificity, 89.7%; sensitivity, 62.1%). Conclusion: Elevated levels of plasma RIP3 were significantly associated with neurological deterioration and poor prognosis in patients with LAA. A significant increase in plasma RIP3 levels can predict neurological deterioration and the poor prognosis of these patients.
Keywords: modified Rankin Scale